Mechanically Optimize T Cells Activation by Spiky Nanomotors - Fu, Dongmei; Xie, Dazhi; Wang, Fei; Chen, Bin; Wang, Zhen; Peng, Fei (Frontiers in Bioengineering and Biotechnology, 2022)
T cell activation is vital for immune response initiation and modulation. Except for the strength of the interaction between T cell receptors (TCR) and peptides on major histocompatibility complex molecules (MHC), mechanical force, mediated by professional mechanosensitive ion channels, contributes to activating T cells. The intrinsic characteristic of synthetic micro/nanomotors that convert diverse energy sources into physical movement and force, opening up new possibilities for T cell regulation. In this work, Pd/Au nanomotors with spiky morphology were fabricated, and in the presence of low concentrations of hydrogen peroxide fuel, the motors exhibited continuous locomotion in the cellular biological environment. Physical cues (force and pressure) generated by the dynamic performance are sensed by mechanosensitive ion channels of T cells and trigger Ca2+ inﬂux and subsequent activation. The successful demonstration that mechanical signals generated in the bio microenvironment can potentiate T cells activation, represents a potential approach for cell-based cancer immunotherapy.